Primary Granulomatous Angiitis of the Central Nervous System With Amyloid Angiopathy: A Case Report and Literature Review. Issue 3 (February 2015) - Fang, Chen-Wen; Chen, Ying-Chen; Liao, I-Chuang; Lin, Chou-Ching K.
Abstract : Primary angiitis of the central nervous system is a rare idiopathic inflammation of vessels. We report on a 75-year-old male with primary angiitis of the central nervous system and cerebral amyloid angiopathy. He presented with subacute onset of progressive decline in cognitive functions, followed by confusion and coma. Initial brain magnetic resonance imaging favored meningoencephalitis. There was no improvement after treatment with antibiotics. Final diagnosis was proven by brain biopsy. Corticosteroids were given, but without significant improvement. This case is reported because of its rarity and its clinical presentation.